2016
DOI: 10.1038/jes.2016.77
|View full text |Cite
|
Sign up to set email alerts
|

Elemental analysis of infant airborne particulate exposures

Abstract: Air pollution is hypothesized to have negative impacts on infant pulmonary health because of infants' increased rates of respiration and ongoing lung development. The severity and type of impact may differ depending on elemental concentrations. We conducted a study of 21 infants <6 months old whose parents carried a small personal particulate monitoring device (RTI MicroPEM) and GPS unit with the infant for 7 days in January and February 2015. The study area was Utah County, UT, USA. Real-time particulate expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…General population studies of infants and children have only seen a modestly increased risk of hospitalization for respiratory infections associated with TRAP or outdoor air pollution . In addition, infants with BPD may not have the same degree of TRAP exposure as older children and adults with asthma as infants spend over almost 90% of their time indoors …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…General population studies of infants and children have only seen a modestly increased risk of hospitalization for respiratory infections associated with TRAP or outdoor air pollution . In addition, infants with BPD may not have the same degree of TRAP exposure as older children and adults with asthma as infants spend over almost 90% of their time indoors …”
Section: Discussionmentioning
confidence: 99%
“…We also did not capture the presence of other sources of air pollutants, such as fossil fuel power stations. In addition, most infants and young children spend a high proportion of time indoors, and while we did assess for secondhand smoke exposure, we did not assess for other forms of indoor air pollution, such as combustion byproducts from gas stoves or heat. Other studies completed locally in Baltimore have shown that indoor levels of pollution are often higher than simultaneously measured ambient concentrations .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, past studies have sought to evaluate both laboratory and field performance of just one of these instruments or past versions of the instruments compared to commonly used gravimetric instruments. 18,25,[40][41][42][43][44][45][46][47][48] Although there are no evaluation studies to date that have been conducted on the current version of the ECM, except for a pilot study to compare the ECM to the MicroPEM, 40 in rural India. Correlation between the two instruments was also found to be strong in this preliminary field study (Pearson's r = 0.91, 95% CI 0.84-0.95).…”
Section: Discussionmentioning
confidence: 99%